Toward Naturalistic Neuroscience of Navigation: Opportunities in Coral Reef Fish - Givon, Shachar; Pickholtz, Renanel; Pickholtz, Eliezer Y.; Ben-Shahar, Ohad; Kiflawi, Moshe; Segev, Ronen (Frontiers in Neural Circuits, 2022)
The ability to navigate in the world is crucial to many species. One of the most fundamental unresolved issues in understanding animal navigation is how the brain represents spatial information. Although navigation has been studied extensively in many taxa, the key efforts to determine the neural basis of navigation have focused on mammals, usually in lab experiments, where the allocated space is typically very small; e.g., up to one order of magnitude the size of the animal, is delimited by artificial walls, and contains only a few objects. This type of setting is vastly different from the habitat of animals in the wild, which is open in many cases and is virtually limitless in size compared to its inhabitants. Thus, a fundamental open question in animal navigation is whether small-scale, spatially confined, and artificially crafted lab experiments indeed reveal how navigation is enacted in the real world. This question is difficult to study given the technical problems associated with in vivo electrophysiology in natural settings. Here, we argue that these difficulties can be overcome by implementing state of the art technology when studying the rivulated rabbitfish, Siganus rivulatus as the model animal. As a first step towards this goal, using acoustic tracking of the reef, we demonstrate that individual S. rivulatus have a defined home range of about 200 m in length, from which they seldom venture. They repeatedly visit the same areas and return to the same sleeping grounds, thus providing evidence for their ability to navigate in the reef environment. Using a clustering algorithm to analyze segments of daily trajectories, we found evidence of specific repeating patterns in behavior within the home range of individual fish. Thus, S. rivulatus appears to have the ability to carry out its daily routines and revisit places of interest by employing sophisticated means of navigation while exploring its surroundings. In the future, using novel technologies for wireless recording from single cells of fish brains, S. rivulatus can emerge as an ideal system to study the neural basis of navigation in natural settings and lead to ‘electrophysiology in the wild’.